The impact of a curriculum of the self- learning method to learn some basic skills in football Futsal - رغد جمعة سيد أ.د. هدى عبد السميع (الرياضة المعاصرة)
Paying attention to the educational process and upgrading it and its methods became the only major concern of the educational institutions and many of the researchers in order to facilitate the process of providing information to the learner, which helps to improve and develop the performance skill level of the learner, which requires a to avoid making the educational process largely a teacher-centered, whereas the student role is to be only a recipient. Consequently, there is a must to find a new and modern teaching methods focusing on the idea that the student has to have a major role in the educational process, but not in isolation from the teacher, who is a supervisor, dominating and directing the educational process. One of these methods is the self- learning method. Through this method, the goals set in advance can be reached, which were: to recognize the reality of performance skills